Edukasi Penggunaan dan Resistensi Antibiotik Dry Sirup Secara Swamedikasi pada Wali Siswa MI Ar Roudhoh Patrang - Nafisah Isnawati (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
Antibiotics are one of the drugs that have a role to protect and restore health from infectious diseases (Anief, 2010). Antibiotics are chemical substances produced by microorganisms that have the ability to inhibit the growth and even kill other microorganisms. At this time the community still uses a lot of antibiotics, especially dry syrup preparations. Dry syrup is a dry syrup preparation and needs the addition of water and needs to be cornered when you want to use it. Improper use of dry syrup can cause the drug to not function optimally. Non-optimal use of antibiotic preparations can cause harm, one of which is the occurrence of antibiotic resistance. Antibiotic resistance is a condition where bacteria, viruses, fungi and parasites are unable to be killed by antibiotics. This resistance occurs when bacteria become resistant to antibiotics that were initially effective for treating infections caused by these bacteria. Therefore, this activity aims to educate the public about the use of antibiotics to minimize unwanted effects. The implementation method used is counseling sharing knowledge about dry syrup preparations containing antibiotics. Counseling includes the efficacy of anti-biotics, how to use, side effects, how to store properly. The target audience is the guardian of MI Ar Roudhoh Jember students.